Spatiotemporal bio-shielding of bacteria through consolidated geometrical structuring - Satish Kumar Rajasekharan; Moshe Shemesh (npj Biofilms and Microbiomes, 2022)
Abstract The probiotic bacterium Lactobacillus plantarum is often reckoned as a ‘generalist’ for its ability to adapt and survive in diverse ecological niches. The genomic signatures of L. plantarum have shown its intricate evolutionary ancestry and dynamic lifestyles. Here, we report on a unique geometrical arrangement of the multicellular population of L. plantarum cells. Prominently, a phenomenon of the cone-shaped colony formation and V-shaped cell chaining are discovered in response to the acidic-pH environment. Moreover, subsequent cold stress response triggers an unusual cellular arrangement of consolidated bundles, which appeared to be independently governed by a small heat shock protein (HSP 1). We further report that the V-shaped L. plantarum chaining demonstrates potent antagonistic activity against Candida albicans, a pathogenic yeast, both in vitro and in a Caenorhabditis elegans co-infection model. Finally, we deduce that the multifaceted traits manifested by this probiotic bacterium is an outcome of its dynamic flexibility and cellular heterogeneity.